Text and context revisited within a multimodal framework - Gambier, Yves; Lautenbacher, Olli Philippe (Babel-Verlag, 2025)
We are now faced with a flow of documents. But how do all these digital texts circulate between senders and prosumers? Can we assume that texts today are similar in terms of meaning-making, coherence, and interpretation to texts produced, perceived, used before the technological changes? The current developments in textuality require us to re-examine the materiality, contextualization, genres, and readings of these "new" texts. Three decades of the Internet, the Web, have changed our concepts of text and context, our experience of reading, writing, and translating multimodal texts. First, we revisit the concept of text - to understand what is changing. Second, we revisit the concept of context to problematize it in the new framework, in which digital productions are open, fluid, de-/re-textualizing, de-/re-semiotizing, and de-/re-contextualizing texts. How do multimodal texts shed light on these changes, and how do they participate in them? All the articles discuss text and context and highlight different instances of re-contextualization. The whole issue does not pretend to provide definitive answers but will hopefully contribute to making translation scholars aware of the changes and how they will use text and context from now on.
Un flux de documents nous assaille chaque jour. Mais comment tout ce materiau numerique circule-t-il entre les enonciateurs et les consom'acteurs ? Peut-on considerer comme certain que les textes d'aujourd'hui sont identiques, en termes de fabrique de sens, de coherence, d'interpretation, a ceux d'hier - produits, percus et utilises avant les changements technologiques ? Ces changements exigent de reexaminer la materialite, la contextualisation, les genres, la lecture de ces << nouveaux >> textes. Trois decennies d'Internet et du Web ont transformes nos concepts de texte et de contexte, notre experience de lecture, de redaction, de traduction de ces textes multimodaux. Dans cette perspective, nous nous attachons d'abord a revoir le concept de texte - pour mieux apprehender ce qui change. Puis nous questionnons le concept de contexte de maniere a le problematiser dans ce nouveau cadre ou les productions numeriques sont ouvertes, fluides, de-/ re-textualisant, de-/ re-semiotisant, de-/ recontextualisant les textes. Comment les textes multimodaux eclairent-ils a la fois le changement et y participent-ils ? Tous les articles rassembles dans ce numero discutent du texte et du contexte et traitent de diverses occurrences de la recontextualisation. On n'y pretend pas apporter des reponses definitives ou stables, mais esperons que les chercheurs en traductologie seront sensibilises aux changements en cours et emploieront dorenavant les notions de texte et de contexte en pesant leurs mots.